Analysis of Nigerian lecturers’ professional development programme participation - Awodiji, Omotayo Adewale; Oyedoyin, Michael Mayowa; Jantuah, Samuel Kwadwo (Journal of Management and Business Education, 2022)
In human capital management, the most imperative thing is to think about the human capital that is skillful, innovative, proactive, and profitable for comparative advantage. Any professional development programme (PDP) (Training for Higher Education, Conferences, and Workshops) embarked on by any institution should increase the output and development of both the staff and the university. This study, therefore, sought to investigate lecturers' rate and location of participation in professional development. The rate of participation was investigated using a descriptive survey design. The study participants were all lecturers in Nigerian Federal Universities. The 280 participants were chosen using a stratified sample procedure. The instrument's face, construct, and content validity was done with the internal consistency via Cronbach Alpha indicated 0.70. The research questions were analysed using descriptive statistics (frequency, percentage, graph, mean rating, and rank ordering). Thus, the finding indicated that the Nigerian universities’ lecturers have a high participation rate in PDP. Cross-border training that will enhance university lecturers' productivity should be encouraged more in Nigeria via a Memorandum of Understanding (MoU).